Maternal variants in NLRP and other maternal effect proteins are associated with multilocus imprinting disturbance in offspring. Issue 7 (24th March 2018) - Begemann, Matthias; Rezwan, Faisal I; Beygo, Jasmin; Docherty, Louise E; Kolarova, Julia; Schroeder, Christopher; Buiting, Karin; Chokkalingam, Kamal; Degenhardt, Franziska; Wakeling, Emma L; Kleinle, Stephanie; González Fassrainer, Daniela; et al.
Abstract : Background: Genomic imprinting results from the resistance of germline epigenetic marks to reprogramming in the early embryo for a small number of mammalian genes. Genetic, epigenetic or environmental insults that prevent imprints from evading reprogramming may result in imprinting disorders, which impact growth, development, behaviour and metabolism. We aimed to identify genetic defects causing imprinting disorders by whole-exome sequencing in families with one or more members affected by multilocus imprinting disturbance. Methods: Whole-exome sequencing was performed in 38 pedigrees where probands had multilocus imprinting disturbance, in five of whom maternal variants in NLRP5 have previously been found. Results: We now report 15 further pedigrees in which offspring had disturbance of imprinting, while their mothers had rare, predicted-deleterious variants in maternal effect genes, including NLRP2, NLRP7 and PADI6 . As well as clinical features of well-recognised imprinting disorders, some offspring had additional features including developmental delay, behavioural problems and discordant monozygotic twinning, while some mothers had reproductive problems including pregnancy loss. Conclusion: The identification of 20 putative maternal effect variants in 38 families affected by multilocus imprinting disorders adds to the evidence that maternal genetic factors affect oocyte fitness and thus offspring development. Testing for maternal-effect genetic variants should be considered in families affected by atypical imprinting disorders.